Letting people flourish: defining and suggesting skills for maintaining and improving positive health - Sponselee, Hanne C. S.; ter Beek, Lies; Renders, Carry M.; Kroeze, Willemieke; Fransen, Mirjam P.; van Asselt, Kristel M.; Steenhuis, Ingrid H. M. (Frontiers in Public Health, 2023)
The concept of ‘positive health’ emerged from the need for a holistic and more dynamic perspective on health, emphasising the ability of individuals to adapt and self-manage. The positive health conversation tool helps understand how people score on six positive health dimensions. However, skills within these dimensions to maintain or improve health have not yet been described. This is important for enabling individuals to put health advice into practice. Therefore, this paper aims to define and suggest skills for maintaining and improving positive health. Suggestions for definitions of skills within the positive health dimensions are described using the functional, interactive, and critical health literacy framework. Additionally, executive functions and life skills were incorporated. Moreover, the environment’s role in these individual skills was noted, mentioning organisational health literacy that emphasises organisations’ responsibility to provide comprehensible health information to all individuals. We propose that health promotion interventions can incorporate the proposed skills in practical exercises while aligning intervention materials and implementation tools with end-users and implementers. The suggested skills for maintaining and improving positive health are a first step towards a more comprehensive understanding and open to discussion. These skills may also be applied to other practical conversation tools for maintaining or improving health. Increasing positive health through the defined skills may be especially relevant to those with a lower socioeconomic position who also have limited health literacy and thereby may contribute to reducing health inequalities. Taken together, strengthening the defined skills may hopefully contribute to allowing people to flourish in life.